A Frege‐Geach Style Objection to Cognitivist Judgment Internalism. (September 2014) - Sander, Thorsten
Abstract According to (cognitivist) judgment internalism, there is a conceptual connection between moral judgment and motivation. This paper offers an argument against that kind of internalism that does not involve counterexamples of the amoralist sort. Instead, it is argued that these forms of judgment internalism fall prey to a Frege‐Geach type argument.